Persepsi Perokok Aktif Terhadap Label Pictorial Health Warning pada Masyarakat Desa Rumah Kabanjahe - Sitepu, Kristian Adi Putra; Ritonga, Syafruddin (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2014)
In the wake of this study by the Government Regulation No. 109 of 2012 on the inclusion of images and text health warnings / pictorial health warnings on cigarette packs. The norm of this aims to reduce the negative health effects, protect productive age population and increasing public awareness of the dangers of smoking. Against the background of the norm of the government, the study was intended to determine the perception of active smokers the pictorial health warning labels on packs of cigarettes there. In this study, the method used is descriptive method with qualitative data. Data collected through library research informant interviews, and documentation. The results showed that smokers know their pictorial health warning labels on packs of cigarettes and smokers can understand the meaning of their label. Knowledge smokers against pictorial health warning label does not make the smokers to quit smoking, they continue to smoke because of their experience does not suffer due to take up smoking, and the effects felt far different from what was stated on the packaging that has been made. Thus we can say the perception of smokers tend to deny the existence of the warning label.